Indolylglycines Backbones in the Synthesis of Enantiopure 3, 3‐Spiroindolenines, Indolyl Tetracyclic Hemiaminals, and 3‐Indolyl‐maleimides Frameworks. Issue 33 (29th July 2019) - Markus, Jozef; Ferko, Branislav; Berkeš, Dušan; Moncol, Ján; Lawson, Ata Martin; Othman, Mohamed; Daïch, Adam
Abstract : This paper describes the synthesis of novel N ‐substituted 3‐indolylglycines (3IGs), in high yields and optical purity via three‐component Mannich reaction (3CR) of indole and free glyoxylic acid in the presence of primary and secondary aliphatic amines. By using this efficient approach, a series of racemic 3‐indolylglycines (3IGs) as well as the optically pure ( S )‐3‐indolylglycine (( S) ‐3IG) in multigram synthesis using ( R ‐1‐phenylethylamine (( R )‐α‐PEA) as chiral pool were synthetized. In parallel investigations, 3IGs were used as the starting material for the highly stereoselective synthesis of spiroindolenines bearing three controlled contiguous stereogenic centers. Despite our expectations, the N ‐chloroacetyl esters of 3IGs did not provide the expected spiroindolenine derivatives but led us to the discovery of a new methodology for the preparation of 3‐indolylmaleimides (3IMs); compounds known for their broad range of important biological and fluorescence activities. Abstract : Racemic and enantiopure 3‐indolylglycines (3IGs) were synthesized in high yields and optical purity by using a simple and efficacious Mannich 3CR. A multigram synthesis using ( R )‐PEA as chiral auxiliary was realized. The resulting 3IGs were used to provide enantiopure 3, 3‐spiroindolenines, indolyl tetracyclic hemiaminals, and 3‐indolylmaleimides following an unexpected pathway.